Penerapan Sistem Informasi E-Catalog Perpustakaan pada SMPK St. Yohanes Wewewa Barat - Jefrianus Adi Ama; Stefanus D.I. Mau; Emirensiana Dappa Ege (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
This research aims to develop an E-Catalog Information System for the Library of SMPK St. Yohanes Wewewa Barat as a digital platform that provides students and teachers with fast, accurate, and efficient access to book collection information. The system is designed to replace the previous manual book search process, which often caused delays and reduced the effectiveness of library services. The development of this system applies The Model-View-Controller (MVC) method structures the system by dividing it into three distinct parts: the model, the view, and the controller, each with its own specific function resulting in a structured architecture that is easier to manage, maintain, and improve. This method was chosen because it supports modular development and provides flexibility for future system enhancements. The results of this study show that the developed e-catalog system functions properly and performs well according to the intended design. All main features, including book searching, book detail display, and book data management, operate optimally without significant issues. Moreover, the system helps improve the efficiency of library services and enhances the user experience in accessing digital book information.